Interrelation Of Turkestan Ridge And Foothills - Alisher Turgunov; Sarvinoz Baymuradova (International Scientific and Current Research Conferences, 2020)
The exchange of matter and energy between the Turkestan ridge and its foothills has been studied and analyzed.